Lana's Airship, 1670 (1902)
1902 "Lana's Airship, 1670" [t0470.jpg], 1902, Tressell, Robert This article by Robert Noonan (Tressell) illustrated with his own drawings, was probably written around 1902 and is the only other of his writings to survive besides 'The Ragged Trousered Philanthropists'. It is not known whether it was ever published. Tressell's biographer, Fred Ball mentions his interest in aeronautics and model aircraft in 'One of the Damned'.